HYGIENIC BASICS OF HARDENING OFTEN ILLNESS CHILDREN OF PRESCHOOL AGE - Sidikova Maryam Amankeldievna (Web of Journals Publishing, 2024)
The morbidity of preschool children remains high, despite the successes of preventive medicine. The structure of morbidity is dominated by acute respiratory viral infections [1,3,9,12,14,15]. It is well known that the best means of preventing colds is hardening. There is an extensive literature devoted to this, characterized by many conflicting recommendations [1,5,6,7]. Therefore, the choice of adequate hardening methods should be based on a comprehensive study of the morphofunctional development of children.
Keywords: often sick children, hardening, principles of hardening, health procedures.